Stem cell nanoengineering - Baharvand, Hossein; Aghdami, Nasser, 1971- (Hoboken, New Jersey : Wiley Blackwell, 2014)
Stem Cell Nanoengineeringreviews theapplications ofnanotechnology in the fields of stem cells, tissue engineering, and regenerative medicine. Topics addressed include various types of stem cells, underlying principles of nanobiotechnology, the making of nano-scaffolds, nano tissue engineering, applications of nanotechnology in stem cell tracking and molecular imaging, nano-devices, as well asstem cell nano-engineering from bench to bedside. Written by renowned experts in their respective fields, chapters describe and explore a wide variety of topics in stem cellnanoengineering, making the book a valuable resource for both researchers and clinicians in biomedical and bioengineering fields.
Delivery of molecules and genes/siRNA into stem cells by nanoengineering / Mohsen Ashjari -- Expansion of stem cells by nano-tissue engineering / Amir Mellati, Hu Zhang -- Nano-tissue engineering of neural cells / Sasan Jalili-Firoozinezhad, Fahimeh Mirakhori, Hossein Baharvand -- Nanotechnology and cardiovascular tissue engineering / Savneet Kaur, Upasana Rishiraj -- Nano-tissue engineering of musculoskeletal cells / Mohamadreza Baghaban Eslaminejad, Leila Taghiyar, Fatemeh Safari -- Nano-tissue engineering of skin cells / Daisy M. Ramos, Aditi Subramanian, Aja Aravamudhan, Matthew Harmon, Roshan James, Kottappally Thankappan Shalumon, Ahmed Nada, Sangamesh G. Kumbar -- High-throughput screening of stem cell self-renewal and differentiation on nanomaterials / Perry T. Yin, Tae-Hyung Kim, Jeong-Woo Choi, Ki-Bum Lee -- Nanotechnology for cellular imaging / Miroslaw Janowski, P. Walzcak, J.W.M. Bulte -- Advancing translational nanotechnology to clinical application / Michelle Griffin, Shima Salmasi, Nima Naderi, Peter E. Butler, Alexander M. Seifalian.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Stem cells; Nanobiotechnology; Stem Cells; Cell Engineering; Nanostructures; Nanotechnology; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Nanobiotechnology; Stem cells; Electronic books